The impact of COVID-19 on EU-China trade flows - Dominika Choroś Mrozowska (Comparative Economic Research. Central and Eastern Europe, 2022)
COVID-19 is expected to have contributed towards changing the geographical structure of world trade, including trade between individual EU countries and China. This article presents the results of an analysis of the impact of the COVID-19 pandemic on Sino-EU trade flows. The research aims to ascertain whether European Union countries noted a strengthening of their competitive advantage in trade with China in any of the 21 HS sections by increasing the value of the normalized revealed comparative advantage index (NRCA). To identify and select the most significant NRCA observations, Chebyshev's inequality was used. The analysis was carried out for 2015 to 2020, with a particular emphasis on 2020, when the first effects of the COVID-19 pandemic were recorded. EU-China trade relations have been the subject of numerous studies, but their nature has not yet been fully elucidated. This article tries to fill that gap. The analysis of mutual trade, especially at such an important moment from the socio-economic perspective, can bring significant results. The analysis revealed that the pandemic did not result in any decline in EU-China trade. In fact, global trade rose in 2020, with most of the 27 EU countries recording increases in both imports and exports. There were also no significant changes in the structure of the distribution of comparative advantage. However, in contrast to the previously analyzed years (2015-2019), in 2020, the NRCA index shows a flatter distribution, suggesting that most EU countries with the highest comparative advantages actually observed reductions in them.
Keywords: F10; F140; 330; COVID-19; international trade; import; export; normalized revealed comparative advantage